Pengaruh Regulasi dan Sistem Informasi terhadap manajemen aset pada Pemerintah Kabupaten Aceh Timur - Iqlima Azhar; Safuridar Safuridar; Syardiansah Syardiansah (Universitas Putera Batam, 2020)
This study aims to examine the effect of regulations and information systems on asset management in the East Aceh District Government. The research was carried out on employees of the goods section of the East Aceh District Government Offices. Data collection was carried out through primary data, namely by distributing questionnaires to each respondent. Determination of the sample used in this study is the census method with a total sample of 44 people. The results showed that there is a significant relationship between regulation and information systems on asset management. This is indicated by the coefficient of determination (R2) of 0.773 or 77.3% of asset management is influenced by regulations and information systems, while the remaining 23% is influenced by other variables outside of this study.